Ecology and field biology of two dominant Camponotus ants (Hymenoptera: Formicidae) in the Brazilian savannah. Issue 3 (25th January 2018) - Ronque, Mariane U.V.; Fourcassié, Vincent; Oliveira, Paulo S.
Abstract : Camponotus renggeri and C. rufipes are very abundant in Brazilian cerrado savannah, where they feed extensively on liquid rewards and commonly associate with plants bearing extrafloral nectaries and honeydew-producing insects. Here, we provide a qualitative and quantitative field account on the natural history and ecology of these two ant species. The study was carried out in a cerrado reserve in south-eastern Brazil across a rainy/hot season (summer) and a dry/cold season (winter). The ants were found in two vegetation physiognomies: all nests of C. rufipes were located in the cerrado sensu stricto (scrub of shrubs and trees, 3–8 m tall), whereas C. renggeri occurred mostly in the cerradão (forest with more or less merging canopy, 10–12 m tall). Both species nested in fallen or erect dead trunks, as well as underground. In addition, C. rufipes built nests using dead plant material arranged or not around shrub bases. Colonies of C. rufipes were generally more populous than those of C. renggeri, and both species had colonies with more than one dealated queen. Both species were active mainly at night and foraged for resources near their nests, mainly extrafloral nectar and hemipteran honeydew (aphids and mealybugs). The average size of the home ranges of C. renggeri in cerrado sensu stricto and cerradão varied from ≈ 2.8 to 4.0 m 2 and apparently were not affected by season. In C. rufipes, however, foraging grounds in cerrado sensu stricto showed a twofold increase from dry/cold (≈ 4.5 m 2 ) to rainy/hot season (≈ 9.8 m 2 ). Our study highlights the importance of natural history data to understand the foraging ecology and role of these ants in cerrado savannah.